Earmarking Risk: Relational Investing and Portfolio Choice. (22nd April 2020) - Hayes, Adam; O'Brien, Rourke
Abstract: Ordinary individuals are increasingly charged with making investment decisions not only for themselves but also for close others. A child's college savings account and a spouse's retirement savings are instances where investing has become unmistakably relational. In this paper, we posit a theory of relational investing that extends Zelizer's relational perspective from the domain of transactions to that of financial risk-taking. Through two original survey experiments, we demonstrate that (1) individuals are less risky with dollars earmarked for others, (2) risk tolerance varies as a function of for whom the dollars are earmarked, and (3) labeling accounts for culturally significant life-stage events (such as retirement or college) also shapes risk tolerance. Because allocation decisions determine financial returns achieved by portfolios invested in the market, our framework and findings have important implications for understanding potential drivers of wealth inequality as well as for the study of culture and economic behavior.